2009
DOI: 10.1152/ajpheart.00983.2008
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CYP2J2 provides protection against doxorubicin-induced cardiotoxicity

Abstract: Human cytochrome P-450 (CYP)2J2 is abundant in heart and active in biosynthesis of epoxyeicosatrienoic acids (EETs). Recently, we demonstrated that these eicosanoid products protect myocardium from ischemia-reperfusion injury. The present study utilized transgenic (Tr) mice with cardiomyocyte-specific overexpression of human CYP2J2 to investigate protection toward toxicity resulting from acute (0, 5, or 15 mg/kg daily for 3 days, followed by 24-h recovery) or chronic (0, 1.5, or 3.0 mg/kg biweekly for 5 wk, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 63 publications
5
63
0
1
Order By: Relevance
“…All experiments complied with the requirements of the University of Kentucky Institutional Animal Care and Use Committee. The animal treatment protocols were based on studies demonstrating decreased cardiac function after chronic treatment with DOX (Zhang et al, 2009). All experiments used male mice aged 10-12 weeks weighing 25-35 g. Mice were administered intraperitoneal DOX (Pfizer, NY) at a dose of 3 mg/kg body weight (protocol A) or 2 mg/kg body weight (protocol B), or an equivalent volume of saline, twice a week for 3 or 5 weeks, resulting in a cumulative DOX dose of 18 mg/kg (protocol A) or 20 mg/kg (protocol B) (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments complied with the requirements of the University of Kentucky Institutional Animal Care and Use Committee. The animal treatment protocols were based on studies demonstrating decreased cardiac function after chronic treatment with DOX (Zhang et al, 2009). All experiments used male mice aged 10-12 weeks weighing 25-35 g. Mice were administered intraperitoneal DOX (Pfizer, NY) at a dose of 3 mg/kg body weight (protocol A) or 2 mg/kg body weight (protocol B), or an equivalent volume of saline, twice a week for 3 or 5 weeks, resulting in a cumulative DOX dose of 18 mg/kg (protocol A) or 20 mg/kg (protocol B) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The authors thank Dr. John Seubert (University of Alberta, Edmonton, AB, Canada) for numerous helpful discussions regarding the chronic DOX treatment model (Zhang et al, 2009). Conducted experiments: Zhang.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Recently, Zhang et al reported mice with cardiomyocyte specific overexpression of CYP2J2 had reduced doxorubicin-induced cardiotoxicity. The reduced toxicity was partially attributed to increased metabolism of doxorubicin by microsomes prepared from CYP2J2 hearts (17). Exposure to drugs, such as cocaine, can induce the CYP expression in the heart (60).…”
Section: Cyp Metabolism and Cardiotoxicity In The Heartmentioning
confidence: 99%
“…These EETs have many biological functions including, but not limited to, angiogenesis, regulation of vasodilation, inhibition of cytokine-induced endothelial cell adhesion-molecule expression, inhibition of vascular smooth muscle cell migration, protection of endothelial cells against hypoxia-reoxygenation injury, upregulation of endothelial nitric oxide biosynthesis, and protection of doxorubicin-induced cardiotoxicity (Larsen et al, 2007;Spector and Norris, 2007;Yang et al, 2009;Zhang et al, 2009;Campbell and Fleming, 2010;Pfister et al, 2010). All these events are involved in cardiac electrophysiology and protect the heart from ischemic-reperfusion injury (Spiecker and Liao, 2006).…”
Section: Introductionmentioning
confidence: 99%